(untitled) (Research, Society and Development, 2021)
The coexistence between tourism, weather and climate has already been represented by several regional and world studies, the objective is to carry out an analysis of the rainfall indices between the period from 1913 to 2016 aiming at supporting urban and rural tourism in the municipality of Caruaru. This analysis is relevant, since the studied area is characterized by a rainfall variability and a diversity of rainfall impacts of great significance in the studied area. The pluviometry data were acquired from the Pernambuco State Water and Climate Agency, where statistically simplified calculations were used to define mean, standard deviation, coefficient of variance, maximum and minimum absolute values. Quarter and the rainy and dry month. The municipality has potential landscaping and trade for tourism activities. The rain did not prove to be an impediment to the practice of tourism. Year was registered with conditions favorable to the practices of recreation and leisure. The month of June with moderate to strong rains on weekends may have totally hampered the tourist activities of the field, in the other months the rainfall indices indicated good conditions for its rural and urban tourism development. In the dry period, there was a reduction for rainfall and isolated and occasional rains of varying magnitude were recorded in a short period.